5‐alpha‐reductase inhibitors and the risk of diabetes mellitus: A nationwide population‐based study. Issue 1 (22nd September 2015) - Lee, Shang‐Sen; Yang, Yu‐Wan; Tsai, Tsung‐Hsun; Kuo, Yu‐Hung; Chuang, Hsun‐Yang; Lee, Ching‐Chih; Hsieh, Teng‐Fu
Abstract : BACKGROUND: This nationwide population‐based study investigated the risk of type 2 diabetes mellitus (DM) after 5‐alpha‐reductase inhibitor (5ARI) therapy for benign prostate hyperplasia (BPH) using the National Health Insurance Research Database (NHIRD) in Taiwan. METHODS: In total, 1, 298 adult patients newly diagnosed with BPH and who used more than 28 cumulative defined daily doses (cDDD) of 5ARI were recruited as the therapy group cohort, along with 1, 2887 subjects who did not use more than 28 cDDD of 5ARI as a control group from 2002 to 2009. Each patient was monitored for 5 years (from 2003 to 2008) to identify those who subsequently developed type 2 DM. A Cox proportional hazards model was used to compare the risk of type 2 DM between the study and comparison cohorts after adjusting for possible confounding risk factors. RESULTS: Patients who received 5ARI therapy had a lower cumulative rate of type 2 DM than those who did not receive 5ARI during the five‐year follow‐up period (3.5% vs. 5.3%, P  = 0.003). In sub‐group analysis, among the BPH patients aged <65 years, the five‐year type 2 DM events hazard ratio (HR) of 5ARI users was lower than that of nonusers (HR: 0.47, 95% confidence interval (CI): 0.24–0.91; P  = 0.026). CONCLUSIONS: Therapy with 5ARI may decrease the five‐year risk of type 2 DM in the BPH patients younger than 65 years. Further mechanistic research is warranted to validate the results. Prostate 76:41–47, 2016 . © 2015 Wiley Periodicals, Inc.